(untitled) (Journal of Medical & Health Sciences Review, 2025)
Granulomatous inflammation is an orchestrated inflammatory reaction that develops to entrap persistent pathogenic organisms, typically Mycobacterium tuberculosis in tuberculosis (TB) and fungi such as Aspergillus, Histoplasma, and Mucor species. Since these infections can resemble each other on radiography and routine histopathology, either necrotizing or non-necrotizing granulomas, conventional diagnostic tests like Ziehl-Neelsen (ZN) staining, fungal special stains like periodic acid-Schiff (PAS) and Gomori methenamine silver (GMS), microbiological culture, and PCR can be lowly sensitive in the paucibacillary disease. Immunohistochemistry (IHC) has become a useful supplement as it allows direct visualization of pathogen-specific antigens like Mycobacterium tuberculosis protein-64 (MPT64), Antigen-85 complex (Ag85), and lipoarabinomannan (LAM) and visualization of immune markers such as cluster of differentiation 68 (CD68), cluster of differentiation 4 (CD4), cluster of differentiation 8 (CD8), interferon-gamma (IFN-γ), and tumor necrosis factor-alpha (TNF-α). IHC, based on genus-specific antigens, has higher sensitivity in fungal granulomas with inconclusive PAS or GMS results. The IHC is a highly valuable diagnostic tool despite its drawbacks, including the loss of antigens in necrotic tissue or the possibility of cross-reactivity, which enhances diagnostic accuracy and differentiation between tuberculous and fungal granulomatous infections and is therefore of great importance in high-burden areas.